Development of a curriculum in international journals from 2004 to 2007 - Salve, Guilherme Bizarro; Cazarini, Edson Walmir (Revista Gestão da Produção Operações e Sistemas, 2010)
The offer of quality courses is a concern of education organizations. The use of curriculum development, in engineering courses, can contribute towards its fitness, the needs of productive sectors, society and students. The paper aims to map the “state of the art” on the subject. In particular, the bibliographic production of inter-national English journals, from 2004 to 2007 has been characterized. The procedures were systematized and differences in existing concepts were mapped. The Thesaurus describer “curriculum development” was used as a key word. Twenty-eight papers were selected. The outcome demonstrated that existing research is dispersed in diverse publication media and there is a proportional diversity of authors, resulting in article discontinuity in journals and works by the same author. Approximately 68% of the works use participant research for achie-ving objectives. It was ascertained that most authors use a resume project approach, which contrasts with the most complete vision. It is important to understand this conceptual difference, since it is the cause of distinc-tions in research and development results in the area.Keywords: Curriculum; Development; Engineering; Improvement.